Associations between nine dietary minerals intake and all-cause mortality in individuals with atherosclerotic cardiovascular disease - Duan, Chenglin; Lv, Meng; Shou, Xintian; Chen, Zizhen; Luan, Yujie; Hu, Yuanhui (Frontiers in Nutrition, 2024)
Background Varied intake of dietary minerals critically affects cardiovascular health. This study examines the associations of nine dietary minerals intake with all-cause mortality in atherosclerotic cardiovascular diseases (ASCVDs). Methods This study analyzed 4,125 individuals with ASCVD from the National Health and Nutrition Examination Survey, employing Kaplan–Meier survival analyses, weighted Cox models, and restricted cubic splines to assess linear and nonlinear relationships between dietary minerals intake and all-cause mortality. Associations across different body mass index (BMI) categories were also evaluated separately. Results Over 6.25 years of median follow-up, 1,582 deaths were documented. Adjusted for potential covariates, results show a negative linear correlation between dietary magnesium intake and all-cause mortality (p for trend <0.001). Compared to the lowest quartile, all-cause mortality risk in the highest quartile was found to be 0.63 (95% CI 0.49–0.81). The associations between intake of the other eight dietary minerals and all-cause mortality were not robust. BMI significantly influenced the links between dietary minerals intake and all-cause mortality (p for interaction <0.05). Across BMI categories, significant negative associations were found between intake of magnesium, phosphorus, potassium, sodium, and copper and all-cause mortality in underweight or normal weight groups. In overweight individuals, intake of calcium, iron, magnesium, and potassium was negatively linked to all-cause mortality. For obese groups, sodium intake negatively affected all-cause mortality (p for trend <0.001). Conclusion Unlike other dietary minerals, increased magnesium intake significantly reduced all-cause mortality risk in ASCVD. BMI influenced the associations between dietary minerals intake and all-cause mortality.